COVID-19 Treatment—Current Status, Advances, and Gap - Chian Ho; Lee, Ping Chin (MDPI, 2022)
COVID-19, which emerged in December 2019, was declared a global pandemic by the World Health Organization (WHO) in March 2020. The disease was caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It has caused millions of deaths worldwide and caused social and economic disruption. While clinical trials on therapeutic drugs are going on in an Accelerating COVID-19 Therapeutic Interventions and Vaccines (ACTIV) public–private partnership collaboration, current therapeutic approaches and options to counter COVID-19 remain few. Therapeutic drugs include the FDA-approved antiviral drugs, Remdesivir, and an immune modulator, Baricitinib. Hence, therapeutic approaches and alternatives for COVID-19 treatment need to be broadened. This paper discusses efforts in approaches to find treatment for COVID-19, such as inhibiting viral entry and disrupting the virus life cycle, and highlights the gap that needs to be filled in these approaches.